A technology-enhanced scaffolding instructional design for fully online courses - Yang, Juan; Jiang, Rui; Su, Han (Australasian Journal of Educational Technology, 2022)
The COVID-19 pandemic has forced teachers to implement fully online teaching. This study reviewed the popular technologies that are used in online learning, as well as the advantages and difficulties of applying fully online courses for formal education. Based on this research background, this study proposed a nested scaffolding design of an online course for 215 college students in China with the help of six technological tools, which effectively replaced face-to-face interactions and significantly improved the usage of the supporting learning platform. The inner-outer learning cycles supported by the technological tools improved the quality of the scaffolding conversations, reduced the scaffolding time cost that teachers had to expend and enhanced the effectiveness of the individualised scaffolding instructions. Implications for practice or policy: First-year students’ learning outcomes can be improved by the scaffolding support from Web 2.0 resource URLs, a small private online course, and EducCoder resources. Course leaders should construct at least 3–5 stage-wise evaluations to deconstruct the big learning process into several observable learning cycles, making the Kolb (1984) cycles controllable. Assessors may need to consider involving various exercises, such as quizzes, online experiments and synthesised tasks to facilitate students’ learning.